Inclusion of interleukin-6 improved the performance of postoperative acute lung injury prediction for patients undergoing surgery for thoracic aortic disease - Li, Huili; Feng, Weiqi; Wang, Qiuji; Li, Chenxi; Zhu, Jiade; Sun, Tucheng; Wu, Jinlin (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background: We studied acute lung injury (ALI) in thoracic aortic disease (TAD) patients and investigated the predictive effect of interleukin-6 (IL-6) in acute lung injury after thoracic aortic disease. Methods: Data on 200 TAD patients, who underwent surgery between January 2016 to December 2021 at our hospital, were studied. We analyzed acute lung injury using two patient groups. Patients with No-ALI were 65 and those with ALI were 123. Univariate logistic, LASSO binary logistic regression model and multivariable logistic regression analysis were performed for acute lung injury. Results: Preoperative IL-6 level was lower (15.80[3.10,43.30] vs 47.70[21.40,91.60] pg/mL, p < 0.001) in No-ALI group than in ALI group. The cut-off points, determined by the ROC curve, were preoperative IL-6 > 18 pg/mL (area under the curve: AUC = 0.727). Univariate logistic regression analysis showed 19 features for TAD appeared to be early postoperative risk factors of acute lung injury. Using LASSO binary logistic regression, 19 features were reduced to 9 potential predictors (i.e., Scrpost +PLTpost + CPB>182min+ D-dimerpost +D-dimerpre+ Hypertension+ Age>58 years+ IL6>18 pg/ml +IL6). Multivariable logistic regression analysis showed that Postoperative creatinine, CPB>182 min and IL-6 >18 pg/ml were early postoperative risk factors for ALI after TAD, and the odds ratios (ORs) of postoperative creatinine, CPB>182 min and IL-6 >18 pg/ml were 1.006(1.002-1.01), 4.717(1.306-19.294) and 2.96（1.184-7.497), respectively. When postoperative creatinine, CPB>182 min and IL-6 >18 pg/ml (AUC = 0.819), the 95% confidence interval [CI] was 0.741 to 0.898. Correction curves were nearly diagonal, suggesting that the nomogram fit well. The DCA curve was then drawn to demonstrate clinical applicability. The DCA curve showed that the threshold probability of a patient is in the range of 30% to 90%. Conclusions: The inclusion of interleukin-6 demonstrated good performance in predicting ALI after TAD surgery.